Kajian Spesial dan Buka Puasa Bersama: Strategi Meningkatkan Partisipasi Keagamaan di Desa Purnakarya: Special Study and Breaking the Fast Together: Strategy to Increase Religious Participation in Purnakarya Village - Jahada Mangka; Irsyad Rafi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
STIBA Makassar Real Work Lecture (KKN) Batch VII in Punakarya Village, Tanralili District, Maros Regency, was carried out as a form of community service which is one of the main pillars of the Tri Dharma of Higher Education. This research aims to analyze how to optimize community religious development by students through the KKN program. The program implementation method begins with mapping community problems and needs using the SOAR Analysis (Strengths, Opportunities, Aspirations, Results) approach. Based on the results of this analysis, work programs are prepared that are relevant to community needs. The programs implemented include Imam & Tarawih Lectures, Dirosa Teaching, TPA/TPA Teaching, Kilat Islamic Boarding School, Teaching in Schools, Special Study & Breaking the Fast Together, Arba'in Book Reading, Funeral Service Training, and Imam and Friday Sermons. All of these programs were implemented well and showed initial results that were in line with the main objective of KKN, namely making a real contribution to religious formation and development of local communities.